Florentino Pérez: wizjoner, strateg, lider - Kubiaczyk, Filip (Studia Europaea Gnesnensia, 2023)
Ramón Álvarez de Mon, Florentino. Viaje hacia elReal Madrid del siglo XXI, Editorial Corner, Barcelona 2023, ss. 201